Urban green areas in Belém of Pará: history, and potentialities of the environmental Park Antonio Danúbio Lourenço da Silva (Research, Society and Development, 2020)
Parks and gardens are estate of the revaluation of naturalistic ideals, mainly European, and perform social, aesthetic and ecological functions. The study aimed to identify the historical, educational, recreational and urban development aspects that involve and / or exert pressure in Parque Ambiental Antonio Danúbio, in the Region Metropolitan of Belém/PA, contributing to its valorization as an area of ​​biodiversity conservation and quality of life for the population. Non-participant observation techniques and semi-structured interviews were applied. 35 people were heard who are in any way related to the area. Throughout its history, the Park area has undergone actions of different natures, which have changed the structure, organization and function, mainly in the vegetation physiognomy, resulting from the rapid and unplanned urban expansion. The Park faces old problems with the lack of resources, however, it is still a place of pleasant climate, contemplation of nature and can be a space of educational, cultural and memory of the population.